Pembelajaran Berkarakteristik dan Inovatif Abad 21 pada Materi Letak dan Luas Benua Asia dan Benua lainnya dengan Model Pembelajaran Problem Based Learning di SMP Negeri 1 Adiwerna Kabupaten Tegal - Rochmat Witono (Cakrawala: Jurnal Pendidikan, 2022)
Problem Based Learning as a learning model that is proven to have an influence or impact on positive learning outcomes on students from various levels of education classes and various subjects mentioned above, is appreciated by the Government of the Republic of Indonesia, which is designated as a learning model in learning practice using the 2013 Curriculum. Problem Based Learning is thus also applied to learning Social Sciences or Social Sciences subjects, of course adjusted to the 2013 Curriculum. Social studies learning at SMP Negeri 1 Adiwerna Tegal, Central Java has used the Problem Based Learning model in accordance with the 2013 Curriculum, but has not been implemented in conjunction with a scientific approach. Even if you use a combination of Problem Based Learning learning models with a scientific approach, you don't use media, especially authentic photos, as an aid in learning. From these various backgrounds, the researchers are interested in conducting research with the title "The Effectiveness of Problem Based Learning Models in Increasing Students' Motivation and Learning Outcomes in Social Studies Subjects at SMP Negeri 1 Adiwerna